PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 6 SEPOTONG - Defri Maulana; A, Syahrilfuddin A, Syahrilfuddin; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated problems that occur in the classroom students V of SD Negeri 6 Sepotong that poor performance in the first semester mathematics learning. This is evident from the number of students who reached KKM many as 6 people (33,3%) while 12 (66,7%) did not reach KKM with an average of 59,722 study results. Based in this background, the researchers have conducted studies class actions (PTK) by implementing cooperative learning model number heads together (NHT). The classroom action research is carried by two cycles. At the first meeting of cycle I of the activities of teachers percentage is 54,16% sufficient criteria at the second meeting of teacher activity increased 66,67% both criteria. In cycle II of the third meeting of teachers increased activity both criteria 70,83% while the fourth meeting the cycle II of teachers increased activity percentage to 87,50% criterion very well. At the first meeting of cycle I of the activities of studenst percentage is 50,00% sufficient criteria at the second meeting of students activity increased 62,50% both criteria. In cycle II of the third meeting of students increased activity both criteria 66,67% while the fourth meeting of cycle II of students increased activity 79,16% criterion very well. For the result of student mathematics learning prior to action average value 59,722 and then increased 64,722 at cycle I with the percentage increase 8,37% and the cycle II of the average value of learning outcomes increased by 73,61% with percentage increase of 23,26% study resultKeyword : Cooperative model number heads together (NHT), learning result of mathematics